2020
DOI: 10.21203/rs.3.rs-23855/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Levels, Trends and Determinants of Technical Efficiency of General Hospitals in Uganda: Data Envelopment Analysis and Tobit Regression Analysis

Abstract: Background General hospitals provide a wide range of primary and secondary healthcare services. They accounted for 38% of government funding to hospitals, 8.8% of OPD visits and 28% of admissions in Uganda in FY 2016/17. We assessed the levels, trends and determinants of technical efficiency of general hospitals in Uganda from FY 2012/13 to FY 2016/17.Methods We undertook input-oriented Data Envelopment Analysis to estimate technical efficiency of 78 general hospitals using data abstracted from the Annual Heal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In other words, either output expansion or input decrease is the primary evaluation goal. More than half of the studies (55.06%, 49 of 89) [46][47][48][50][51][52][53][54]58,60,[64][65][66][67][68][69][71][72][73][75][76][77]80,[91][92][93][94]96,98,99,[103][104][105][106][107][109][110][111][113][114][115][116]118,121,124,127,128,130,135] applied input-orientated DEA models. The researchers indicated that the choice of input orientation was made to be in line with th...…”
Section: Model Orientationmentioning
confidence: 99%
“…In other words, either output expansion or input decrease is the primary evaluation goal. More than half of the studies (55.06%, 49 of 89) [46][47][48][50][51][52][53][54]58,60,[64][65][66][67][68][69][71][72][73][75][76][77]80,[91][92][93][94]96,98,99,[103][104][105][106][107][109][110][111][113][114][115][116]118,121,124,127,128,130,135] applied input-orientated DEA models. The researchers indicated that the choice of input orientation was made to be in line with th...…”
Section: Model Orientationmentioning
confidence: 99%